Quantification of number of CD38 sites on bone marrow plasma cells in patients with light chain amyloidosis and smoldering multiple myeloma - Kriegsmann, Katharina; Dittrich, Tobias; Neuber, Brigitte; Awwad, Mohamed; Hegenbart, Ute; Goldschmidt, Hartmut; Hillengaß, Jens; Hose, Dirk; Seckinger, Anja; Müller-Tidow, Carsten; Ho, Anthony Dick; Schönland, Stefan; et al. (Cytometry. Part B, Clinical cytometry, 2018)
Background Recent approaches in multiple myeloma (MM) treatment have targeted CD38. As antigen expression levels on plasma cells (PCs) were demonstrated to affect response to monoclonal antibody (mAb) treatment, a precise characterization of PC phenotype is warranted. Methods Anti-CD38 mAb (isatuximab) was tested for antibody-dependent cellular cytotoxicity (ADCC) in MM cell lines. Quantification of the number of sites (NOS) of CD38 on bone marrow PCs and other immune cells obtained from light chain (AL) amyloidosis (n = 46) and smoldering multiple myeloma (SMM) patients (n = 19) was performed with two different quantitative flow cytometry (QFCM) applications. Results ADCC activity of isatuximab was observed in cell lines with >100 × 103 CD38-NOS only. The average PC CD38-NOS was 153 ± 53 × 103 in AL amyloidosis and 138.7 ± 53 × 103 in SMM patients. Eight (17%) AL amyloidosis and 4 (21%) SMM patients showed a PC CD38-NOS level <100 × 103. In four AL amyloidosis and two SMM patients <10% of PCs had a CD38-NOS ≥100 × 103. The CD38-NOS identified on bone marrow lymphocytes, monocytes, and granulocytes was two log units below the CD38-NOS on PCs (P < 0.001). No significant differences in CD38-NOS expression levels on any of the analyzed PC subpopulations in AL amyloidosis and SMM patients were identified. Conclusion Levels of CD38 expression affect the isatuximab-mediated ADCC in vitro. As PCs of patients with AL amyloidosis and SMM do not homogenously express high CD38 our data provide a rationale for assessment of CD38-NOS in patients with PC disorders prior to anti-CD38 treatment. © 2018 International Clinical Cytometry Society